Use of GIS in the improvement of sewage treatment plant management: A case study - Kabbashi, Nassereldeen Ahmed; Al-Khatib, Ma'an Fahmi Rashid; Abdul Malek, Mohd Izhar (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Sewage treatment plant (STP) is a facility designed to treat wastewater. It helps to reduce the concentration of pollutant prior to release to the environment. Efficient and effective management of STP is very important nowadays. Late in decision making or overcoming operational problem might incur high repairing cost which in the end will badly effect the organization. GIS is a tool that has good potential in improving the management issue of the treatment plant. The system offers a better way to handle all information related to STP and at the same time provides a geographic context for the facilities. ArcGIS is a software developed by ESRI, was used in this project to show location of all STP in IIUM. Other relevant information was also stored such as number of population in mahallah and flow rate of wastewater from mahallah. Some options were highlighted to improve the management of sewage sludge with composting was highlighted as the suggested method. Finally, the performance of STP was discussed and some recommendations were given for future work.